Somaliland: Fraternity in Female Key. Rhymed Resistance for Peace (1991-1996) - Mata Carnevali, María Gabriela (2024)
In the postmodern pluralist vein that opens the way to new ways of reading texts and history, the bicentenary of the French Revolution (1789) awakened a renewed interest in its principled triad in general, but above all in fraternity as a political category. Its importance for peace-building and the evolution of democracies became clear from the first studies carried out in Europe and Latin America. This article discusses fraternity in the context of the formation and consolidation of Somaliland as an independent state from Somalia (1991-1996), and its relevance to the debate on civil resistance and the different nonviolent forms of struggle. Given the undisputed prominence of women, especially women poets, it is possible to underline the importance and particularities of female participation in this kind of movements and the relevance of the arts as a means of struggle.